Features of the Legal Status of Maritime Areas around Svalbard Archipelago - Y. G. Shipilov; E. S. Lisitsa (Евразийская интеграция: экономика, право, политика, 2019)
Spitsbergen (Svalbard) - polar archipelago located in the Arctic Ocean. The Svalbard Treaty was signed in 1920, granting full sovereignty to Norway. But despite the fact that the question of the legal status of Spitsbergen resolved, there still controversy about the sensible features and conditions of this sovereignty. In this article, a special place is given to the status of the waters around Svalbard. As for the Russian fisheries in the Barents and Norwegian Seas, including sea area of Svalbard, it has important historical significance, as well as being important in terms of production of living resources. However, after the establishment of Norway's 200-mile fisheries protection zone around Svalbard other countries emerged some difficulties in the public domain in the maritime spaces around the archipelago. This article is devoted to the development problems of interpretation of the provisions of the Svalbard Treaty of Paris in 1920.